Implementasi Manajemen Sarana Prasarana Pendidikan di Sekolah Menengah Atas (SMA) dalam Rangka Peningkatan Mutu Pembelajaran - Rahma Zhafirah, Alya; Nurlaeli, Acep; Ma'shum, Sya'roni (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Educational facilities and infrastructure are very important to support learning activities in every school, especially in facilitating an effective learning process. This study aims to explain how the management of facilities and infrastructure can improve the quality of learning at SMAN 3 Karawang. Management of educational facilities and infrastructure includes planning, organizing, implementing, monitoring, and evaluating. This study used a qualitative approach with data collection techniques in the form of interviews, observations, and documentation, involving respondents such as the head of infrastructure and school principal. Data analysis was done by reducing, presenting, and drawing conclusions. The results showed that the implementation of educational facilities and infrastructure management at SMAN 3 Karawang has met the set standards, allowing optimal utilization for learning activities and school administration, thus contributing to the overall improvement of school quality.